WORKING WITH A MULTICULTURAL SOCIETY - Rosita Tandos (Asia-Pacific Journal on Religion and Society, 2021)
Along with the development process and globalization impact, the world recently becomes closer and inter-dependence. Responding such global situation, multiculturalism comes to offer solution for a wide range  of issues  associated  with  individual, cultural, ethnical and religious diversities. Understand this sense, multiculturalism is not an optional extra, or it is not something that society want to have it or avoid. For any societies, they need to work for manage diversity not sufficient with celebrating and acknowledging it. Then, social interventions and services  at  any  aspects  of  life  (social,  cultural,  education,  economic  and  political)  need  to integrate  the notion of integrity  and diversity  as parts of multiculturalism.  This paper aims to introduce the need  for understanding  multiculturalism  as a process  that  is always  contextual, affecting significantly on community organizing and education programs.